A CLINICAL CASE OF METHEMOGLOBINEMIA IN A GASTROENTEROLOGY PATIENT - Sarycheva, Elena Germanovna (Mother and Baby in Kuzbass, 2026)
A detailed clinical case of drug-induced methemoglobinemia in a child following treatment with an antacid containing a local anesthetic is presented. This study provides a clear treatment algorithm, including discontinuation of the offending drug, administration of specific antidote therapy, and follow-up. The conclusion emphasizes the need for increased clinical vigilance for this life-threatening condition when prescribing commonly used medications, as well as the importance of using co-oximetry to confirm the diagnosis.